Aluminum connection material
By controlling the shape ratio of Si phase and AL phase in the AL connecting material and adding appropriate elements, the fatigue problem of AL connecting material under high temperature cycle conditions is solved, and the reliability and initial bonding strength improvement in high-speed temperature cycle test are achieved.
Patent Information
- Application Number
- JP2024536441
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2023-11-27
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2043-11-27
AI Technical Summary
Existing AL connecting materials are prone to fatigue and damage under high-temperature cycling conditions, making it difficult to meet the temperature cycling reliability and initial bonding strength requirements of next-generation power semiconductor equipment, especially in high-speed temperature cycling tests.
By controlling the short side length to long side length ratio (e/f) of the Si phase in the AL connecting material and the short side length ratio (c/d) of the AL phase, and adding appropriate amounts of Sr, Eu, Na and other elements to form a uniformly distributed Si phase and AL phase, the thermal fatigue resistance and primary bonding strength of the material are improved.
In the high-speed temperature cycle test, the temperature cycle reliability and initial bonding strength of the AL connecting material are significantly improved, the fatigue damage of the material is reduced, and the stable operation of the semiconductor equipment is ensured.
Smart Images

Figure 0007626906000004 
Figure 0007626906000005 
Figure 0007626906000006
Abstract
Description
[Technical field]
[0001] The present invention relates to an Al connecting material. [Background technology]
[0002] In semiconductor devices, electrodes formed on a semiconductor chip are connected to electrodes on a lead frame or a substrate by bonding wires (wire material) or bonding ribbons (strip material). In power semiconductor devices, bonding wires and bonding ribbons made of aluminum (Al) are mainly used. The wire diameter of Al bonding wires is mainly in the range of 100 μm to 600 μm, and the width of Al bonding ribbons is mainly in the range of 100 μm to 3000 μm, and the thickness is mainly in the range of 50 μm to 600 μm. Here, Al bonding wires and Al bonding ribbons are collectively called Al connection materials.
[0003] In power semiconductor devices, silicon (Si) is often used as the material for the semiconductor chip, and Al-Si alloys or Al-Cu alloys are often used as the material for the electrodes formed on the semiconductor chip. Power semiconductor devices using Al connecting materials are often used as high-power devices such as air conditioners and solar power generation systems, and as semiconductor devices for vehicles.
[0004] There are two methods for joining Al connecting materials: the first joining with electrodes on a semiconductor chip, and the second joining with electrodes on a lead frame or substrate, both of which use wedge joining. Wedge joining is a method in which ultrasonic vibration and load are applied to the Al connecting material via a metal tool, destroying the surface oxide film on the Al connecting material and the electrode material, exposing the new surface, and performing solid-state diffusion bonding. This joining method is characterized by the fact that it connects the connecting material in a solid state without melting it, and is a joining technology that differs from welding technology, which melts the connecting material.
[0005] Next-generation power semiconductor devices are required to operate stably for a long period of time compared to general-purpose power semiconductor devices. Power semiconductor devices operate by repeatedly turning current on and off. When current is supplied to a Si semiconductor chip through an Al connecting material, the temperature of the first junction rises. On the other hand, when the current supply is stopped, the temperature of the first junction drops. In this way, the first junction repeatedly rises and falls in temperature during operation of the power semiconductor. As a result, thermal stress caused by the difference in thermal expansion between the Al connecting material and the semiconductor chip is repeatedly applied to the first junction. When a connecting material made only of high-purity Al is used, the Al connecting material breaks down in a relatively short time due to thermal stress, making it difficult to satisfy the performance required for next-generation power semiconductor devices. Therefore, next-generation power semiconductors are required to improve the junction life (hereinafter also referred to as "temperature cycle reliability") associated with the rise and fall of temperature of the first junction.
[0006] In response to the demand for temperature cycle reliability, aluminum interconnect materials have been proposed that focus on improving mechanical strength. As a method for improving the mechanical properties of aluminum interconnect materials, a method of adding specific elements to aluminum has been proposed.
[0007] Patent Document 1 discloses a bonding wire made of an Al alloy containing at least magnesium (Mg) and silicon (Si) and having a total content of Mg and Si of 0.03% by mass to 0.3% by mass. This patent document discloses that the decrease in the bonding strength of the first bonding part in a cold-temperature cycle test in the temperature range from 70°C to 120°C is delayed due to the effect of increasing the strength by solid solution strengthening of Mg and Si and the effect of suppressing crack growth by precipitated magnesium silicide (Mg2Si).
[0008] Patent Document 2 discloses a bonding wire made of an alloy containing 0.01-0.2 mass% iron (Fe), 1-20 mass ppm silicon (Si), and the remainder being Al with a purity of 99.997 mass% or more, in which the amount of Fe in solid solution is 0.01-0.06%, the amount of Fe precipitated is 7 times or less the amount of Fe in solid solution, and the wire has a fine structure with an average crystal grain size of 6-12 μm. This patent document discloses that the mechanical strength of the matrix is improved by uniformly dispersing intermetallic compound particles of Fe and Al in Al, and the recrystallized grains are further refined, thereby suppressing a decrease in the bonding strength of the 1st bonding portion in a thermal shock test in a temperature range of -50°C to 200°C.
[0009] Patent Document 3 discloses a bonding wire obtained by melting an Al-Si alloy containing 0.1 to 5 mass% silicon (Si) with the remainder being Al and impurities, and then extruding and quenching the melted Al-Si alloy to form it into a thin wire. This patent document discloses that mechanical strength is improved by quenching the molten Al-Si alloy to finely and uniformly disperse Si. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2014-131010 A [Patent Document 2] JP 2014-129578 A [Patent Document 3] Japanese Patent Application Publication No. 59-57440 Summary of the Invention [Problem to be solved by the invention]
[0011] As described above, the next-generation power semiconductor device is required to be able to withstand longer use than the general-purpose power semiconductor device. During the operation of the power semiconductor device, the temperature of the first joint repeatedly rises and falls. As a result, since the Al connecting material has a larger linear expansion coefficient than the semiconductor chip, thermal stress occurs in the first joint due to the difference in linear expansion coefficient between the two, and the Al connecting material may eventually be fatigued. A temperature cycle test is one of the tests for accelerating evaluation of the life (temperature cycle reliability) of the joint associated with the rise and fall in temperature of the first joint. The Al connecting material used in the next-generation power semiconductor is required to exhibit excellent temperature cycle reliability in a temperature cycle test. However, when an Al connecting material with high strength due to the addition of Si or the like as disclosed in Patent Documents 1 to 3 is used, in a temperature cycle test assuming use in the next-generation power semiconductor device, it has been confirmed that there is a problem that cracks progress at a relatively high speed in the Al alloy electrode, which has a lower strength than the Al connecting material, and it is difficult to stably obtain good temperature cycle reliability.
[0012] Conventional temperature cycle tests (hereinafter, also referred to as "TCT") can be easily performed using commercially available test equipment. However, the rate of change of temperature in TCT is relatively slow, and there is concern that it may deviate from the fast rate of change of temperature during the operation of power semiconductor devices. Recently, therefore, in order to bring the temperature change rate closer to the conditions of actual use, high-speed temperature cycle tests (hereinafter, also referred to as "high-speed TCT"), which increase the temperature change rate, have been considered. The rate of change of temperature is, for example, about 10°C / min in conventional TCT, whereas in high-speed TCT, the temperature changes at a high speed of, for example, about 200°C / min. Regarding the reliability evaluation of the joints of Al connecting materials, even if the reliability of an Al connecting material does not decrease when evaluated by conventional TCT, there are cases where the joint strength decreases and the joint life is shortened when evaluated by high-speed TCT. Therefore, there is a demand for Al connecting materials that exhibit good joint reliability even in high-speed TCT, which is a more severe test that is closer to the conditions of actual use, and that provide excellent temperature cycle reliability. Hereinafter, the temperature cycle reliability in high-speed TCT may be referred to as "high-speed temperature cycle reliability".
[0013] In addition, if a bonding failure occurs during bonding, such as the peeling off of the Al connecting material from the electrode, this leads to product defects and a decrease in manufacturing yield, so it is required to obtain good bonding strength at each bonding part. In this regard, if ultrasonic vibration or load is applied strongly to the 1st bonding part in order to obtain good bonding strength, the semiconductor chip may be damaged. In particular, when an Al connecting material strengthened by adding Si or the like is used, the semiconductor chip is easily damaged during the 1st bonding due to its hardness, and when the ultrasonic vibration or load is adjusted to reduce such damage, the bonding area cannot be stably secured due to its high deformation resistance and instability of the deformation direction, so that sufficient bonding strength of the 1st bonding part (hereinafter, also simply referred to as "1st bonding strength") cannot be obtained in some cases. These problems at the initial bonding of the 1st bonding part eventually cause a decrease in temperature cycle reliability and instability, which is an obstacle to practical use of the Al connecting material strengthened by adding Si or the like.
[0014] An object of the present invention is to provide an Al connecting material that satisfies excellent temperature cycle reliability and good first bonding strength. [Means for solving the problem]
[0015] As a result of intensive research into the above-mentioned problems, the inventors have found that an Al connecting material containing 3.0 mass% or more and 12.0 mass% or less of Si, and one or more of Sr, Eu, and Na in total at 5 mass ppm or more and 800 mass ppm or less, in which the average ratio (e / f) of the short side length e to the long side length f of the Si phase in the L cross section (cross section in the central axis direction including the central axis) of the Al connecting material is within a specific range, can solve the above-mentioned problems, and have completed the present invention through further research based on this knowledge.
[0016] That is, the present invention includes the following. <1> An Al connecting material containing 3.0 mass% or more and 12.0 mass% or less of Si and containing one or more of Sr, Eu, and Na in total in an amount of 5 mass ppm or more and 800 mass ppm or less, An Al connecting material, in which the average ratio (e / f) of the short side length e to the long side length f of the Si phase in the L cross section (cross section in the central axis direction including the central axis) of the Al connecting material is 0.25 or more and 0.65 or less. <2> The average ratio (c / d) of the short side length c to the long side length d of the Al phase in the L cross section is 0.25 or more and 0.7 or less. <1> The Al connecting material described in <3> The average diameter of the Al phase in the L cross section is 5 μm or more and 40 μm or less. <1> or <2> The Al connecting material described in <4> Further, it contains one or more of Fe, Mg, Mn, Ga, and Ge in a total amount of 5 ppm by mass to 700 ppm by mass. <1> ~ <3> The Al connecting material according to any one of the preceding claims. Effect of the Invention
[0017] According to the present invention, it is possible to provide an Al connecting material that satisfies excellent temperature cycle reliability and good first bonding strength. [Brief description of the drawings]
[0018] [Figure 1] Fig. 1 is a schematic diagram for explaining the measurement surface (inspection surface) when measuring the shapes (shape ratio (e / f) and shape ratio (c / d)) and average diameter of the Si phase and Al phase of an Al connecting material. The measurement surface is a cross section (L cross section) in the central axis direction including the central axis of the Al connecting material. [Diagram 2] FIG. 2 is a schematic diagram for explaining the short side length (e) and long side length (f) of the Si phase in the L cross section. [Diagram 3] FIG. 3 is a schematic diagram for explaining the short side length (c) and long side length (d) of the Al phase in the L cross section. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present invention will be described in detail below based on preferred embodiments. Although the drawings may be referred to in the description, each drawing merely shows the shape, size and arrangement of components to the extent that the invention can be understood. The present invention is not limited to the following embodiments and examples, and may be modified and implemented as desired within the scope of the claims of the present invention and their equivalents.
[0020] [Al connection material] The Al connecting material of the present invention contains 3.0 mass% or more and 12.0 mass% or less of Si, and contains at least one of Sr, Eu, and Na (hereinafter also referred to as the "first element group") in a total amount of 5 mass ppm or more and 800 mass ppm or less, The Al connecting material is characterized in that the average ratio (e / f) of the short side length e to the long side length f of the Si phase in the L cross section (cross section in the central axis direction including the central axis) is 0.25 to 0.65.
[0021] As mentioned above, in the temperature cycle test (TCT), when a connecting material made of only high-purity Al is used, cracks propagate relatively fast inside the connecting material, making it difficult to obtain good temperature cycle reliability. On the other hand, when an Al connecting material strengthened by adding Si or the like is used, cracks propagate inside the Al alloy electrode, which has a relatively low strength, so it was confirmed that it is difficult to obtain the temperature cycle reliability required for next-generation power semiconductor devices. That is, in a high-speed temperature cycle test (high-speed TCT) in which the temperature change rate is accelerated, which is close to the conditions of actual use, it was confirmed that even an Al connecting material whose reliability does not decrease when evaluated by the conventional TCT may experience a decrease in bonding strength and a shortened bonding life. Furthermore, when an Al connecting material strengthened by adding Si or the like is used, the semiconductor chip is easily damaged during the 1st bonding, and when the ultrasonic vibration or load is adjusted to reduce such damage, sufficient 1st bonding strength may not be obtained.
[0022] As a result of intensive research to solve the above problems, the inventors have found that an Al connecting material containing 3.0 mass% to 12.0 mass% Si and a total of 5 mass ppm to 800 mass ppm of at least one of the first element group, in which the average ratio (e / f) of the short side length e to the long side length f of the Si phase in the L cross section is 0.25 to 0.65, can improve temperature cycle reliability and 1st bond strength. Such an Al connecting material of the present invention significantly contributes to realizing the temperature cycle reliability required for next-generation power semiconductor devices and to realizing good 1st bond strength.
[0023] The Al connecting material of the present invention contains 3.0 mass% to 12.0 mass% of Si, and is composed of an Al phase in which Si is dissolved in Al, and a Si phase formed by crystallization or precipitation of Si. Here, the Al phase may contain other additive elements in addition to Si. The Si phase is a general term for Si crystallized particles and Si precipitates. The Si crystallized particles are formed from the melt during solidification and are coarse with a size of about 1 to 20 μm, while the Si precipitates are formed from the solid state and are small with a size of about 0.1 to several μm.
[0024] In the present invention, the L cross section of the Al connecting material, i.e., the cross section in the central axis direction including the central axis of the Al connecting material, is as will be explained later in the section "(Method of measuring the shapes of the Si phase and Al phase)" with reference to Figure 1.
[0025] The reason why the Al connecting material of the present invention can provide excellent temperature cycle reliability and good first bonding strength is presumed to be as follows.
[0026] Regarding temperature cycle reliability, for Al joint materials containing high concentrations of Si, the Si phase crystallized during solidification has a smaller linear expansion coefficient than Al, which contributes to reducing the difference in linear expansion coefficient between the Al joint material and the semiconductor chip, and thus reduces the thermal stress that occurs, improving the joint reliability in normal TCT. However, in high-speed TCT, where the temperature change rate is fast, severe thermal fatigue occurs, and it may be difficult to satisfy strict reliability requirements by adding Si alone. In detail, in Al joint materials containing high concentrations of Si, the Si phase tends to coarsen in a plate-like or columnar shape and its distribution tends to be localized, but if there are areas with a large amount of Si phase and areas with a shortage of Si phase at the same time, concentration of strain is likely to occur during high-speed TCT, resulting in a decrease in joint life. In response to this, it is thought that the addition of a certain amount of the first element group can have the effect of refining the Si phase in the Al joint material and distributing it almost uniformly throughout the Al joint material. It is presumed that the uniform distribution of the Si phase alleviates the concentration of strain during high-speed TCT and improves the life.
[0027] As for the first bonding strength, as mentioned above, it is considered that the addition of a predetermined amount of the first element group can have the effect of refining the Si phase in the Al connecting material and distributing it almost uniformly throughout the Al connecting material. The uniform distribution of the Si phase can stabilize the deformation of the Al connecting material in the direction perpendicular to the ultrasonic vibration when ultrasonic vibration and load are applied. Furthermore, it is considered that the control of the shape of the Si phase (ratio (e / f)) can improve the adhesion in the central axis direction of the interface between the Si phase and the Al phase, thereby controlling the interface slippage when ultrasonic vibration and load are applied, thereby increasing the bonding strength.
[0028] It is presumed that by simultaneously achieving uniform distribution of the Si phase and controlling the shape of the Si phase using the first element group, it is possible to promote plastic deformation in the directions perpendicular and parallel to the central axis of the Al connecting material, thereby increasing the joint strength, and also to improve the joint reliability in high-speed TCT by dispersing thermal fatigue in the joint.
[0029] -Si concentration- The Si concentration in the range of 3.0 mass% or more and 12.0 mass% or less reduces the thermal distortion of the joint and helps to improve the temperature cycle characteristics. If it is less than 3.0 mass%, the improvement effect is small, and if it exceeds 12.0 mass%, problems such as a decrease in initial joint strength due to hardening and damage to the semiconductor chip occur. From the viewpoint of obtaining good temperature cycle reliability even in a high-speed TCT with a high temperature change rate close to the conditions of actual use, the concentration of Si in the Al connecting material of the present invention is 3.0 mass% or more, preferably 3.5 mass% or more, more preferably 3.6 mass% or more, 3.8 mass% or more, 4.0 mass% or more, 4.2 mass% or more, 4.4 mass% or more, 4.5 mass% or more, 4.6 mass% or more, 4.8 mass% or more, or 5.0 mass% or more. On the other hand, if the hardness of the Al connecting material is excessive, damage to the semiconductor chip is likely to occur during 1st joining under the joining conditions of ultrasonic vibration and load that are generally used. From the viewpoint of obtaining good bonding strength when performing 1st bonding under general bonding conditions, the Si concentration in the Al connecting material of the present invention is 12.0 mass% or less, preferably 11.5 mass% or less or 11.0 mass% or less, and more preferably 10.8 mass% or less, 10.6 mass% or less, 10.5 mass% or less, 10.4 mass% or less, 10.2 mass% or less, or 10.0 mass% or less.
[0030] For example, an ICP (Inductively Coupled Plasma) emission spectrometer or an ICP mass spectrometer can be used to analyze the concentration of elements contained in the Al connecting material of the present invention. If elements derived from atmospheric contaminants such as oxygen and carbon are adsorbed on the surface of the Al connecting material, it is effective to wash the surface with an acid or alkali according to the adsorbed substance before analysis.
[0031] - Concentration of the first group of elements - From the viewpoint of obtaining good temperature cycle reliability even in high-speed TCT and obtaining good 1st bonding strength, the total concentration of the first element group in the Al connecting material of the present invention is 5 mass ppm or more, preferably 10 mass ppm or more, more preferably 20 mass ppm or more, 30 mass ppm or more, 40 mass ppm or more or 50 mass ppm or more, even more preferably 60 mass ppm or more, 80 mass ppm or more or 100 mass ppm or more, and the upper limit is 800 mass ppm or less, preferably 750 mass ppm or less or 700 mass ppm or less, more preferably 650 mass ppm or less or 600 mass ppm or less, even more preferably 580 mass ppm or less, 560 mass ppm or less or 550 mass ppm or less. If the total concentration of the first element group is in the above-mentioned preferred range, it is also beneficial from the viewpoint of easily achieving good 1st bonding strength while suppressing damage to the semiconductor chip.
[0032] -Shape of the Si phase in the L cross section- It was found that in an Al connecting material containing a predetermined concentration of Si and the first element group, when the average ratio (e / f) of the short side length e to the long side length f of the Si phase in the L cross section is in the range of 0.25 to 0.65, good temperature cycle reliability can be obtained even in high-speed TCT, as well as good 1st bonding strength can be obtained.
[0033] The value of this ratio (e / f) is an index showing the flatness. Further explanation will be given with reference to FIG. 2. FIG. 2 is a schematic diagram showing the Si phase in the L cross section of the Al connecting material, and the central axis direction of the Al connecting material corresponds to the horizontal direction (left and right direction) of FIG. 2, and the direction perpendicular to the central axis corresponds to the vertical direction (up and down direction) of FIG. 2. For the Si phase in the L cross section, the above-mentioned "short side length e" corresponds to the dimension shown by the symbol e in FIG. 2. Also, for the Si phase in the L cross section, the above-mentioned "long side length f" corresponds to the dimension shown by the symbol f in FIG. 2. Hereinafter, the ratio (e / f) of the short side length e to the long side length f of the Si phase in the L cross section is also simply referred to as the "shape ratio (e / f) of the Si phase". The value of the shape ratio (e / f) of the Si phase can be obtained by the Grain Shape Aspect Ratio in the analysis software attached to the device.
[0034] In order to obtain good temperature cycle reliability and good 1st bonding strength even in high-speed TCT, it is sufficient that the average value of the shape ratio (e / f) of the Si phase in the L cross section is within the above-mentioned preferred range, and it is not necessary that the shape ratio (e / f) of all the Si phases is in the range of 0.25 to 0.65. For example, the Si phase may have a shape ratio (e / f) of less than 0.25, or may have a shape ratio (e / f) of more than 0.65.
[0035] From the viewpoint of obtaining better temperature cycle reliability even in high-speed TCT and obtaining better 1st joint strength, the average value of the shape ratio (e / f) of the Si phase in the L cross section of the Al connecting material of the present invention is more preferably 0.3 or more, even more preferably 0.32 or more, 0.34 or more, or 0.35 or more, and the upper limit is more preferably 0.6 or less, even more preferably 0.58 or less, 0.56 or less, or 0.55 or less.
[0036] To measure the average value of the shape ratio (e / f) of the Si phase in the L cross section of the Al joint material, a method can be used that combines the information on the Al concentration and Si concentration obtained by SEM-EDS with the information on the crystal orientation obtained by EBSD. In detail, in the measurement area where the L cross section of the Al joint material is used as the inspection surface, the concentration measurement of Al and Si using EDS and the crystal orientation analysis using EBSD are performed simultaneously. Next, the Al phase and the Si phase are separated and extracted from the EDS measurement results using the analysis software attached to the device. Specifically, it is preferable to use the Chi Scan function, which is a function of the analysis software OIM Data Collection or OIM Anaysis (both made by TSL Solutions) attached to the FE-SEM device. Then, for the area identified as the Si phase, the crystal orientation can be analyzed by using the analysis software attached to the device. If the orientation difference between the measurement points is 15° or more, it is determined to be a grain boundary and the ratio (e / f) is calculated. The average value of the shape ratios (e / f) of each Si phase is defined as the average value of the shape ratio (e / f) of the Si phase. In the process of calculating the shape ratio (e / f) of the Si phase, the calculation was performed excluding the parts where the crystal orientation could not be measured, or the parts where the crystal orientation could be measured but the reliability of the orientation analysis was low. Therefore, in one embodiment, the average value of the shape ratio (e / f) of the Si phase in the L cross section of the Al connecting material of the present invention is calculated by the following steps (1) to (3). (1) The L-section of the Al joint material is used as the inspection surface, and the Al and Si concentrations are measured using EDS and the crystal orientation is measured using EBSD simultaneously. (2) Use the Chi Scan function to separate and extract Al and Si. Specifically, by setting a Tolerance equivalent to the Si threshold from the Si EDS measurement results, Al and Si can be separated and identified. The crystal orientation can be analyzed using the Al and Si crystal information from the material file. (3) For the region identified as the Si phase, the crystal orientation is analyzed, and if the orientation difference between the measurement points is 15° or more, it is determined to be a grain boundary, and the shape ratio (e / f) of each grain is obtained. The shape ratios (e / f) of each grain are averaged to calculate the average value of the shape ratio (e / f) of the Si phase. Here, the average value of the shape ratio (e / f) of the Si phase is the value of the Grain Shape Aspect Ratio (hereinafter referred to as the "grain shape aspect ratio") of the analysis software. This value is obtained by averaging the grain shape aspect ratios of each grain. The grain shape aspect ratio is calculated by calculating the ratio (e / f) of the short side length (e) (Grain Shape Minor Axis) and the long side length (f) (Grain Shape Major Axis) of one grain. For the average calculation, the area average that can be selected in the software attached to the device is used. By adopting the average value obtained by area averaging, it is possible to accurately measure and judge whether the conditions related to the average value of the shape ratio (e / f) of the Si phase, which is suitable for obtaining good temperature cycle reliability even in high-speed TCT and good 1st bonding strength, are met. The area average is calculated by averaging the values obtained by multiplying the ratio of each particle area to the total particle area, and is calculated automatically by the software.
[0037] In the above step (2), the Tolerance (%) setting can be selected in the range of 20 to 40%, and in a standard analysis of the L cross section of an Al joint material, it is preferable to compare at about 30%. Here is a supplementary explanation of the procedure for adjusting this Tolerance. It is preferable to select or confirm the Tolerance value so that the shape and size of the Si phase extracted and identified by the Chi Scan function are equivalent to those of the Si phase identified from the EDS map that displays the Si element concentration in EDS analysis in two dimensions.
[0038] In the present invention, the average value of the shape ratio (e / f) of the Si phase was determined as the average value of each value obtained by measuring at three or more points. In selecting the measurement area, from the viewpoint of ensuring the objectivity of the measurement data, it is preferable to obtain measurement samples from the Al connection material to be measured at intervals of 50 cm or more in the central axis direction of the Al connection material and provide them for measurement. In addition, in the present invention, the measurement area of the crystal orientation by the EBSD method is preferably such that the length in the central axis direction of the Al connection material is 300 μm or more and less than 800 μm, and the entire Al connection material is included in the direction perpendicular to the central axis of the Al connection material, but if the size is large and it is difficult to measure the entire Al connection material, it may be adjusted to a range of less than 600 μm.
[0039] -Shape of Al phase in L cross section- In the Al connecting material of the present invention, the average ratio (c / d) of the short side length c to the long side length d of the Al phase in the L cross section is preferably in the range of 0.25 to 0.7.
[0040] Regarding Al connecting materials that contain a high concentration of Si, wire breakage may occur during wire drawing, resulting in a decrease in manufacturing yield. Possible causes of wire breakage include an increase in the drawing force during wire drawing, which causes breakage of the Al phase, and uneven work hardening, which causes localized deformation of the Al phase, which leads to necking and breakage.
[0041] The inventors, in the course of investigating an Al connecting material containing 3.0 mass% to 12.0 mass% Si and a total of 5 mass ppm to 800 mass ppm of at least one kind of a first element group, and having an average value of a shape ratio (e / f) of the Si phase in the L cross section of 0.25 to 0.65, found that the shape of the Al phase in the L cross section affects the frequency of wire breakage during processing. In detail, they found that the frequency of wire breakage during processing is reduced by setting the average value of the ratio (c / d) of the short side length c to the long side length d of the Al phase in the L cross section to a range of 0.25 to 0.7.
[0042] The value of this ratio (c / d) is an index showing the flatness. Further explanation will be given with reference to FIG. 3. FIG. 3 is a schematic diagram showing the Al phase in the L cross section of the Al connection material, and the central axis direction of the Al connection material corresponds to the horizontal direction (left-right direction) of FIG. 3, and the direction perpendicular to the central axis corresponds to the vertical direction (up-down direction) of FIG. 3. For the Al phase in the L cross section, the above-mentioned "short side length c" corresponds to the dimension shown by the symbol c in FIG. 3. Also, for the Al phase in the L cross section, the above-mentioned "long side length d" corresponds to the dimension shown by the symbol d in FIG. 3. Hereinafter, the ratio (c / d) of the short side length c to the long side length d of the Al phase in the L cross section is also simply referred to as the "shape ratio (c / d) of the Al phase." The value of the shape ratio (c / d) of the Al phase can be obtained by the Grain Shape Aspect Ratio in the analysis software attached to the device.
[0043] The reason why the frequency of wire breakage during processing can be reduced by controlling the average value of the shape ratio (c / d) of the Al phase in the Al connecting material of the present invention is presumably as follows. It is believed that controlling the average value of the shape ratio (c / d) of the Al phase in the L cross section within the above range acts to make the deformation of the crystal grains uniform in response to the pressure and tension applied within the Al connecting material during processing. Since the Si phase is hard and hardly contributes to plastic deformation, it is believed that the shape of the Al phase is effective in improving wire breakage defects.
[0044] In order to reduce the frequency of wire breakage during processing, it is sufficient that the average value of the shape ratio (c / d) of the Al phase in the L cross section is within the above-mentioned preferred range, and it is not necessary that the shape ratio (c / d) of all Al phases is in the range of 0.25 to 0.7. For example, the wire may contain an Al phase having a shape ratio (c / d) of less than 0.25, or may contain an Al phase having a shape ratio (c / d) of more than 0.7.
[0045] From the viewpoint of further reducing the frequency of wire breakage during processing, the average value of the shape ratio (c / d) of the Al phase in the L cross section of the Al connecting material of the present invention is more preferably 0.3 or more, even more preferably 0.32 or more, 0.34 or more, or 0.35 or more, and the upper limit is more preferably 0.65 or less, even more preferably 0.64 or less, 0.62 or less, or 0.6 or less.
[0046] For measuring the average value of the shape ratio (c / d) of the Al phase in the L cross section of the Al connecting material, a method can be used that combines information on the Al concentration and Si concentration obtained by SEM-EDS with information on the crystal orientation obtained by EBSD, as in the measurement of the average value of the shape ratio (e / f) of the Si phase. Therefore, in one embodiment, the average value of the shape ratio (c / d) of the Al phase in the L cross section of the Al connecting material of the present invention is calculated by the following steps (1) to (3). (1) The L-section of the Al joint material is used as the inspection surface, and the Al and Si concentrations are measured using EDS and the crystal orientation is measured using EBSD simultaneously. (2) Use the Chi Scan function to separate and extract Al and Si. Specifically, by setting a Tolerance equivalent to the Si threshold from the Si EDS measurement results, Al and Si can be separated and identified. The crystal orientation can be analyzed using the Al and Si crystal information from the material file. (3) For the region identified as the Al phase, the crystal orientation is analyzed, and if the orientation difference between the measurement points is 15° or more, it is determined to be a grain boundary, and the shape ratio (c / d) of each crystal grain is calculated, and the shape ratio (c / d) of each crystal grain is averaged to calculate the average shape ratio (c / d) of the Al phase. Here, the average value of the shape ratio (c / d) of the Al phase is the value of the Grain Shape Aspect Ratio (grain shape aspect ratio) of the analysis software, as in the case of calculating the average value of the shape ratio (e / f) of the Si phase. Also, for the average calculation, the average value calculated by the area average, which can be selected in the software attached to the device, is adopted, as in the case of calculating the average value of the shape ratio (e / f) of the Si phase. By adopting the average value calculated by the area average, it is possible to accurately measure and judge whether the conditions related to the average value of the shape ratio (c / d) of the Al phase, which is suitable for obtaining good temperature cycle reliability even in high-speed TCT and good 1st joint strength, are met.
[0047] When measuring the average value of the Al phase shape ratio (c / d) in the L cross section, the setting range of Tolerance in the above step (2), the method of obtaining the measurement sample, and the measurement area of the crystal orientation by the EBSD method are the same as those described above for the measurement of the average value of the Si phase shape ratio (e / f).
[0048] -Average diameter of Al phase in L section- In the Al connecting material of the present invention, the average diameter of the Al phase in the L cross section is preferably 5 μm or more and 40 μm or less.
[0049] In many cases, the target of the 2nd bonding is a material harder than Al, such as a Cu substrate, and the ultrasonic vibration and load conditions during the 2nd bonding are set higher than those during the 1st bonding, which tends to make the deformation of the Al connecting material, which has been strengthened by adding Si, unstable during the 2nd bonding. In this regard, the present inventors have found that the variation in bonding strength during the 2nd bonding can be reduced by setting the average diameter of the Al phase in the L cross section to a range of 5 μm to 40 μm. The reason for this is believed to be that the effect of promoting the deformation of the Al connecting material by ultrasonic vibration by containing Si and the first element group at a predetermined concentration and controlling the average value of the shape ratio (e / f) of the Si phase within a predetermined range, and the effect of making the deformation of the Al connecting material uniform in both directions parallel and perpendicular to the central axis of the Al connecting material by setting the average diameter of the Al phase to 5 μm to 40 μm work synergistically.
[0050] From the viewpoint of further reducing the variation in the bonding strength in the 2nd bonding and realizing a better stability of the bonding strength, the average diameter of the Al phase in the L cross section of the Al connecting material of the present invention is more preferably 10 μm or more, more preferably 12 μm or more, 14 μm or more, or 15 μm or more. Also, the upper limit of the average diameter of the Al phase in the L cross section is more preferably 35 μm or less, more preferably 30 μm or less, and even more preferably 28 μm or less, 26 μm or less, or 25 μm or less.
[0051] A method for measuring the average diameter of the Al phase in the L cross section of the Al connecting material will be described. For measuring the average diameter of the Al phase in the L cross section, a method of combining information on the Al concentration and Si concentration obtained by SEM-EDS with information on the crystal orientation obtained by EBSD can be used, similar to the measurement of the average value of the shape ratio (e / f) of the Si phase and the average value of the shape ratio (c / d) of the Al phase described above. The detailed procedure may be the same as that described above in relation to the measurement of the average value of the shape ratio (c / d) of the Al phase, that is, the crystal orientation of the region specified as the Al phase can be analyzed by using the analysis software attached to the device. If the orientation difference between the measurement points is 15° or more, it is determined to be a grain boundary and the circle equivalent diameter is calculated. The average value of the circle equivalent diameter of each Al phase is defined as the average diameter of the Al phase. In the process of calculating the average diameter of the Al phase, the calculation was performed excluding the parts where the crystal orientation could not be measured or the parts where the crystal orientation could be measured but the reliability of the orientation analysis was low. Therefore, in one embodiment, the average diameter of the Al phase in the L cross section of the Al connecting material of the present invention is calculated by the following procedures (1) to (3). (1) The L-section of the Al joint material is used as the inspection surface, and the Al and Si concentrations are measured using EDS and the crystal orientation is measured using EBSD simultaneously. (2) Use the Chi Scan function to separate and extract Al and Si. Specifically, by setting a Tolerance equivalent to the Si threshold from the Si EDS measurement results, Al and Si can be separated and identified. The crystal orientation can be analyzed using the Al and Si crystal information from the material file. (3) For the region identified as Al phase, the crystal orientation is analyzed, and if the orientation difference between the measurement points is 15° or more, it is determined to be a grain boundary and the circle equivalent diameter of each crystal grain is calculated. The circle equivalent diameters of each crystal grain are then averaged to calculate the average diameter of the Al phase. Here, for the average calculation, the average value obtained by area averaging, which can be selected in the software provided with the device, is used. By using the average value obtained by area averaging, it is possible to reduce the variation in the bonding strength in the second bonding and accurately measure and judge whether the conditions related to the average diameter of the Al phase, which are suitable for obtaining good bonding strength stability, are met.
[0052] In the present invention, when calculating the average diameter of the Al phase in the L cross section, only Al phases having a diameter (equivalent circle diameter) of 0.5 μm or more are considered. This makes it possible to accurately determine whether the requirement related to the average diameter of the Al phase in the L cross section, which is suitable for improving the stability of the bonding strength in the 2nd bonding, is met.
[0053] When measuring the average diameter of the Al phase in the L cross section, the setting range of Tolerance in the above procedure (2), the method of obtaining the measurement sample, and the measurement area of the crystal orientation by the EBSD method are the same as those described above for the measurement of the average shape ratio (e / f) of the Si phase.
[0054] In addition to the above, there are several other methods for measuring the shape ratio (e / f) of the Si phase, the shape ratio (c / d) of the Al phase, and the average diameter of the Al phase, including binarization processing from the observed image of the L cross section. However, in the present invention, a method that combines the information on the Al concentration and Si concentration obtained by SEM-EDS and the information on the crystal orientation obtained by EBSD, as described above, is used for the following reasons: the present invention is equipped with many measurement functions and can obtain multiple characteristics such as the shape ratio (e / f) of the Si phase, the shape ratio (c / d) of the Al phase, and the average diameter of the Al phase in a single measurement; automatic analysis is possible; and the measurement is easy using widely used equipment and analysis techniques.
[0055] -Addition of Fe, Mg, Mn, Ga, and Ge- The Al connecting material of the present invention may further contain at least one of Fe, Mg, Mn, Ga, and Ge (hereinafter also referred to as "second element group") in a total amount of 5 ppm by mass or more and 700 ppm by mass or less.
[0056] Furthermore, by containing at least one of Fe, Mg, Mn, Ga, and Ge in a total amount of 5 mass ppm to 700 mass ppm, the occurrence of scratches and chipping on the surface of the Al connecting material can be suppressed, and a smooth surface can be formed. In an Al alloy containing Si at a high concentration of 3.0 mass % to 12.0 mass %, the surface hardens, and the Si phase and Al oxide present on the surface fall off, and the surface may be scratched and chipped during wire drawing, resulting in an Al connecting material with large surface irregularities. It is presumed that the addition of the second element group promotes the stabilization of the Al oxide on the surface of the Al connecting material and the reduction of friction between the Al connecting material and the die, thereby reducing scratches and chipping during wire drawing. It is considered that the addition of the second element group in combination with the first element group enhances the effect of suppressing scratches and chipping on the surface of the Al connecting material and forming a smooth surface.
[0057] From the viewpoint of forming an Al connecting material having a smooth surface while suppressing the occurrence of scratches and chipping on the surface, the total concentration of the second element group in the Al connecting material of the present invention is more preferably 10 ppm by mass or more, even more preferably 20 ppm by mass or more, 30 ppm by mass or more, 40 ppm by mass or more, or 50 ppm by mass or more, and the upper limit is more preferably 650 ppm by mass or less, even more preferably 640 ppm by mass or less, 620 ppm by mass or less, or 600 ppm by mass or less, from the viewpoint of easily achieving good 1st bonding strength while suppressing damage to the semiconductor chip.
[0058] When manufacturing the Al connecting material of the present invention, it is preferable to use Al with a purity of 4N (Al: 99.99% by mass or more) as the aluminum raw material, and it is even more preferable to use Al with a purity of 5N (Al: 99.999% by mass or more) or more, which has a lower amount of impurities.
[0059] The Al connecting material of the present invention may further contain elements other than Al, Si, the first element group, and the second element group (hereinafter, also referred to as "other elements"). The total concentration of the other elements in the Al connecting material is not particularly limited as long as the effects of the present invention are not impaired. The total concentration of the other elements may be, for example, 0.5 mass% or less, 0.4 mass% or less, 0.3 mass% or less, 0.2 mass% or less, 0.15 mass% or less, 0.1 mass% or less, 0.08 mass% or less, 0.06 mass% or less, 0.05 mass% or less, 0.04 mass% or less, 0.03 mass% or less, 0.025 mass% or less, 0.02 mass% or less, 0.018 mass% or less, 0.016 mass% or less, 0.015 mass% or less, 0.014 mass% or less, 0.012 mass% or less, or 0.01 mass% or less. The lower limit of the total concentration of the other elements is not particularly limited, and may be 0 mass%.
[0060] In one embodiment, the balance of the Al connecting material of the present invention is composed of Al and inevitable impurities. Therefore, in a preferred embodiment, the Al connecting material of the present invention is composed of Al, Si, and inevitable impurities. In another preferred embodiment, the Al connecting material of the present invention is composed of Al, Si, one or more elements of the first element group, and inevitable impurities. In yet another preferred embodiment, the Al connecting material of the present invention is composed of Al, Si, one or more elements of the second element group, and inevitable impurities. In yet another preferred embodiment, the Al connecting material of the present invention is composed of Al, Si, one or more elements of the first element group, one or more elements of the second element group, and inevitable impurities.
[0061] In a preferred embodiment, the Al connecting material of the present invention does not have a coating mainly composed of a metal other than Al on the outer periphery of the Al connecting material. Here, the "coating mainly composed of a metal other than Al" refers to a coating in which the content of a metal other than Al is 50 mass % or more.
[0062] The Al connecting material of the present invention may be an Al bonding wire or an Al bonding ribbon. When the Al connecting material of the present invention is an Al bonding wire, its wire diameter is not particularly limited, and may be, for example, in the range of 100 to 600 μm. When the Al connecting material of the present invention is an Al bonding ribbon, its rectangular or approximately rectangular cross-sectional dimensions (W×T) are not particularly limited, and, for example, W may be 100 to 3000 μm, and T may be 50 to 600 μm.
[0063] The Al connecting material of the present invention can satisfy excellent temperature cycle reliability and good first bonding strength, and therefore can be suitably used as an Al connecting material for semiconductor devices, particularly as an Al connecting material for power semiconductor devices.
[0064] -Method of manufacturing Al connection material- An example of a method for producing an Al connecting material of the present invention will be described below. Hereinafter, an example will be described in conjunction with the production of an Al bonding wire having a wire diameter of 200 to 400 μm.
[0065] The Al and alloying elements used as raw materials are preferably of high purity. The purity of Al is preferably 99.99% by mass or more, with the remainder being composed of inevitable impurities. The purity of Si, the first element group, and the second element group used as alloying elements is preferably 99.9% by mass or more, with the remainder being composed of inevitable impurities. The Al alloy used for the bonding wire can be produced by loading the Al raw material and the raw material of the alloying elements into a graphite or alumina crucible processed to obtain a cylindrical ingot, and melting it using an electric furnace or a high-frequency heating furnace. The diameter of the cylindrical ingot is preferably Φ6 mm or more and less than 8 mm, taking into consideration the workability in the subsequent processing steps. The atmosphere in the furnace during melting is preferably an inert atmosphere or a reducing atmosphere to prevent excessive oxidation of Al and other elements constituting the wire. The maximum temperature of the molten metal during melting is preferably in the range of 800 ° C or more and less than 1000 ° C, taking into consideration the ease of controlling the shape and size of the Si phase during solidification while ensuring the fluidity of the molten metal. The cooling method after melting can be water cooling, furnace cooling, air cooling, or the like.
[0066] The cylindrical ingot obtained by melting is subjected to solution treatment by heating at high temperature, and then repeatedly subjected to wire drawing using a die to produce wire of the desired diameter. The wire after wire drawing can be used as Al alloy bonding wire by performing final heat treatment in an electric furnace.
[0067] In order to control the shapes of the Si and Al phases in the L cross section (shape ratio (e / f), shape ratio (c / d)) and the grain size of Al, it is effective to control the heat treatment conditions such as solution treatment and final heat treatment, as well as the wiredrawing conditions. During wiredrawing, it is effective to use a lubricant to ensure lubrication at the contact interface between the wire and the die.
[0068] In order to adjust the shape of the Si phase in the L cross section (shape ratio (e / f)), it is effective to control the reduction in area of the wire during solution treatment and wire drawing.
[0069] The temperature range for solution treatment of the ingot is preferably 400°C or higher and lower than 550°C, and the time period is preferably 1 hour or higher and lower than 6 hours. This solution treatment promotes the division and spheroidization of the Si phase crystallized during the solidification process, making it possible to control the shape of the Si phase during the subsequent wire drawing process. For example, when solution treatment is performed at high temperatures, the shape ratio (e / f) of the Si phase tends to increase.
[0070] Regarding wire drawing conditions, it is effective to set the wire area reduction rate per die used during wire drawing to be in the range of 20% to less than 35%. Here, if the wire area reduction rate per die is P1, P1 is expressed by the following formula.
[0071] P1 = {(R2 2 -R1 2 ) / R2 2}×100 In the formula, R2 represents the diameter (mm) of the wire before processing, and R1 represents the diameter (mm) of the wire after processing.
[0072] By adjusting the wire area reduction rate to the above-mentioned high range (high area reduction rate) compared to normal wiredrawing conditions, the entire wire is significantly deformed during die processing, processing strain increases even inside the wire, and the Si phase is aligned in the wire central axis direction, and at the same time, the shape of the Si phase can be adjusted. By combining the control of the solution treatment conditions described above with the control of the wire area reduction rate during wiredrawing, it becomes easy to adjust the shape ratio (e / f) of the Si phase.
[0073] In order to adjust the shape of the Al phase in the L cross section (shape ratio (c / d)), it is effective to control the wire feed speed during wire drawing and the final heat treatment.
[0074] The wire feed speed during wire drawing will be explained. The wire drawing process from the ingot (wire diameter D0) obtained by melting to a wire diameter (intermediate wire diameter: D+0.5 (D0-D)) that is approximately half the final wire diameter (wire diameter D) is called "wire drawing process 1", and the wire drawing process from the intermediate wire diameter to the final wire diameter is called "wire drawing process 2". It is effective to set the wire feed speed in wire drawing process 1 to 5 m / min or more and less than 15 m / min, and the wire feed speed in wire drawing process 2 to 20 m / min or more and less than 50 m / min. By setting the wire feed speed in the above range, it is possible to control both the processing strain and dynamic recrystallization during wire drawing, and it becomes easy to control the shape ratio (c / d) of the Al phase in the L cross section of the wire to the desired range. If necessary, it is possible to control the shape ratio (c / d) of the Al phase with high precision by combining the adjustment of the wire reduction rate in the range of 20% to less than 35% and the adjustment of the wire feed speed.
[0075] Effective conditions for the final heat treatment are a temperature range of 250°C or higher and lower than 350°C, and a time period of 2 hours or higher and lower than 24 hours. The aforementioned processing strain in the wire caused by the wire drawing process is used as the driving force to promote the progress of recrystallization of the Al phase and adjust the shape of the crystal grains. For example, if the final heat treatment is performed at a low temperature for a long period of time, the crystal grains of the Al phase tend to become granular, and the shape ratio (c / d) tends to increase.
[0076] In order to control the average diameter of the Al phase in the L cross section to a range of 5 μm to 40 μm, it is effective to control the growth of crystal grains due to recrystallization of the Al phase by adjusting the temperature and time of the heat treatment at the final wire diameter. It is effective to control the temperature range of the final heat treatment to 250°C or higher and lower than 340°C, and the time range to 5 hours or higher and lower than 24 hours. By performing homogenization treatment at a relatively low temperature and adjusting the amount of solid solution of Si contained in the Al phase, it becomes easy to adjust the recrystallization temperature of the Al phase in the final heat treatment, and the size of the Al phase can be controlled to the desired range.
[0077] In addition, if intermediate heat treatment is performed as necessary, it becomes easy to adjust the conditions of the final heat treatment. Intermediate heat treatment is a heat treatment performed in the middle of the process of processing from an ingot to the final wire diameter. The temperature range of intermediate heat treatment is 250°C or higher and lower than 400°C, and the time is 30 minutes or more and less than 3 hours. It is effective to perform intermediate heat treatment at a wire diameter that is 2.5 to 4.0 times the final wire diameter. By performing intermediate heat treatment, it is possible to reduce the processing strain of the Al phase and advance recrystallization, and by first adjusting the Al phase, it becomes easy to adjust the grain size of the Al phase in the subsequent final heat treatment. For example, if the intermediate heat treatment temperature is increased, the diameter of the Al phase tends to decrease.
[0078] [Semiconductor Devices] A semiconductor device can be manufactured by connecting electrodes on a semiconductor chip to external electrodes on a lead frame or substrate using the Al connecting material of the present invention. As mentioned above, wedge bonding is used for both the first bonding with the electrodes on the semiconductor chip and the second bonding with the electrodes on the lead frame or substrate.
[0079] In one embodiment, the semiconductor device of the present invention includes a circuit board, a semiconductor chip, and an Al connecting material for electrically connecting the circuit board and the semiconductor chip, and is characterized in that the Al connecting material is the Al connecting material of the present invention.
[0080] In the semiconductor device of the present invention, the circuit board and the semiconductor chip are not particularly limited, and a known circuit board and a semiconductor chip that can be used to configure a semiconductor device may be used. Alternatively, a lead frame may be used instead of the circuit board. For example, the semiconductor device may be configured to include a lead frame and a semiconductor chip mounted on the lead frame, as in the semiconductor device described in JP 2020-150116 A.
[0081] Examples of the semiconductor device include various semiconductor devices used in electrical products (e.g., computers, mobile phones, digital cameras, televisions, air conditioners, solar power generation systems, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, aircraft, etc.), and among these, power semiconductor devices are preferred. EXAMPLES
[0082] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the examples shown below.
[0083] (sample) The method of preparing the samples will be described. The raw material Al had a purity of 4N (99.99% by mass or more), with the remainder consisting of inevitable impurities. The alloying elements Si, the first element group (Sr, Eu, Na), and the second element group (Fe, Mg, Mn, Ga, Ge) had a purity of 99.99% by mass or more, with the remainder consisting of inevitable impurities. The Al alloy used for the Al connecting material was produced by loading the Al raw material and the raw material of the alloying elements into an alumina crucible and melting them using a high-frequency heating furnace. The atmosphere in the furnace during melting was an Ar atmosphere, and the maximum temperature of the molten metal during melting was 800°C or more and less than 1050°C. The cooling method after melting was air cooling in the air or water cooling in water.
[0084] A cylindrical ingot with a diameter of 6 mm was obtained by melting, and the ingot was subjected to solution treatment and homogenization treatment, followed by wire drawing using a die and intermediate heat treatment to produce an Al connection material (Al bonding wire) with a diameter of 300 μm. The temperature range of the solution treatment was 400°C or higher and lower than 550°C, and the time was 1 hour or higher and lower than 6 hours. After the solution treatment, a homogenization treatment was performed continuously during cooling. The temperature range of the homogenization treatment was 300°C or higher and lower than 350°C, and the time was 2 hours or higher and lower than 6 hours. The cooling method after the homogenization treatment was air cooling in the atmosphere.
[0085] A commercially available lubricant was used during the wire drawing process, and the wire area reduction rate per die during the wire drawing process was set to 20% to less than 35%. The temperature range of the final heat treatment was set to 250°C to less than 350°C, and the final heat treatment time was set to 2 hours to less than 24 hours.
[0086] In some examples, the wire feed speed in the wire drawing process 1 was 10 m / min or more and less than 15 m / min, and the wire feed speed in the wire drawing process 2 was 20 m / min or more and less than 40 m / min. In some examples, the temperature range of the intermediate heat treatment was 250°C or more and less than 350°C, and the time period was 30 minutes or more and less than 3 hours. The intermediate heat treatment was performed once, with a wire diameter 2.5 to 4.0 times the final wire diameter.
[0087] (Method of measuring element content) The concentration of elements contained in the Al connecting material was measured using an ICP-OES ("PS3520UVDDII" manufactured by Hitachi High-Tech Science Corporation) or an ICP-MS ("Agilent 7700x ICP-MS" manufactured by Agilent Technologies, Inc.) as an analytical device.
[0088] (Method for measuring the shapes of Si and Al phases) The L-section (cross section in the central axis direction including the central axis) of the Al connecting material was used as the inspection surface, and the shapes (ratio (e / f), ratio (c / d)) of the Si phase and the Al phase were measured. In the present invention, the central axis of the Al connecting material and the cross section in the central axis direction including the central axis (L-section) are as shown in FIG. 1. FIG. 1 shows a case where the Al connecting material is an Al bonding wire having a circular cross-sectional shape, but when the Al connecting material is an Al bonding ribbon having a rectangular or approximately rectangular cross-sectional shape with a width W and a thickness T, the central axis refers to the axis passing through the center of the width W and the center of the thickness T, and the L-section refers to a cross section in the central axis direction including the central axis and in the direction of the thickness T. When processing the cross section to expose the L-section of the Al connecting material, it may deviate from the central axis of the Al connecting material. In this case, if the length in the direction perpendicular to the central axis of the L-section is 90% or more of the wire diameter of the Al connecting material (thickness T in the case of a ribbon), it can be considered as a cross section including the central axis.
[0089] In addition, FE-SEM (SU-70 manufactured by Hitachi High-Technologies Corporation) was used for the measurement, and analysis software APEX (for data collection), OIM Data Collection (for chiscan), and OIM Anaysis (for data analysis) manufactured by TSL Solutions were used for the analysis. Three measurement areas were randomly selected at intervals of 50 cm or more in the central axis direction of the Al connecting material, and measurements were performed on the three areas. The measurement area was determined so that the central axis direction of the Al connecting material was 300 μm or more and less than 800 μm, and the entire Al connecting material was included in the direction perpendicular to the central axis. In addition, the main conditions of the EDS and EBSD measurements were set as follows: acceleration voltage was 15 kV, measurement magnification was 350 times, scan speed was 30 to 120 points / second, and measurement interval was in the range of 0.1 to 0.3 μm. Here, if the scan speed is fast, the measurement time can be shortened, but there is a concern that the measurement accuracy of EDS will decrease. It is desirable to select an appropriate scan speed within the above range.
[0090] - Shape of the Si phase - The shape (shape ratio (e / f)) of the Si phase in the L cross section of the Al joint material was measured by a method that combines the information on the Al concentration and Si concentration obtained by SEM-EDS and the information on the crystal orientation obtained by EBSD. In detail, the measurement was carried out according to the following steps (1) to (3). (1) In the measurement area where the L-section of the Al joint was used as the inspection surface, the concentration of Al and Si was measured using EDS and the crystal orientation was analyzed using EBSD simultaneously. (2) The Chi Scan function of the EBSD analysis software was used to separate and extract Al and Si. Specifically, Al and Si were separated and identified by setting a tolerance equivalent to the Si threshold from the Si EDS measurement results. The crystal orientation was analyzed using the crystal information of Al and Si from the material file. Here, the tolerance condition was mainly set to 30%, and was adjusted as necessary. (3) The crystal orientation of the region identified as the Si phase was analyzed, and if the orientation difference between the measurement points was 15° or more, it was determined to be a grain boundary, and the shape ratio (e / f) of each grain was calculated. The shape ratio (e / f) of each grain was then averaged to calculate the average value of the shape ratio (e / f) of the Si phase. Here, the average value of the shape ratio (e / f) of the Si phase was calculated using the value of the Grain Shape Aspect Ratio ("Grain Shape Aspect Ratio") of the analysis software. Here, the grain shape aspect ratio was calculated by automatically calculating the ratio (e / f) of the short side length (e) (Grain Shape Minor Axis) and the long side length (f) (Grain Shape Major Axis) of one crystal grain. Here, the average value calculated by the area average was used for the average calculation.
[0091] The average value of the shape ratio (e / f) of the Si phase was determined as the average value of the values obtained for the three measurement regions by the above steps (1) to (3).
[0092] - Shape of Al phase - The shape of the Al phase (shape ratio (c / d)) in the L cross section of the Al joint material was measured using a method that combined the information on the Al and Si concentrations obtained by SEM-EDS with the information on the crystal orientation obtained by EBSD, in the same way as in the measurement of the shape ratio (e / f) of the Si phase. In detail, after carrying out the above steps (1) and (2), the measurement was carried out according to the following step (3). (3) For the regions identified as Al phase, the crystal orientation was analyzed, and if the orientation difference between the measurement points was 15° or more, it was determined to be a grain boundary, and the shape ratio (c / d) of each crystal grain was calculated. The shape ratios (c / d) of each crystal grain were then averaged to calculate the average value of the Al phase shape ratio (c / d). Here, the average value of the Al phase shape ratio (c / d) was calculated using the value of the Grain Shape Aspect Ratio ("grain shape aspect ratio") from the analysis software, as in the measurement of the average value of the Si phase shape ratio (e / f), and the average value calculated by the area average was used for the average calculation.
[0093] The average value of the shape ratio (c / d) of the Al phase was determined as the average value of the values obtained for the three measurement regions by the above steps (1) to (3).
[0094] (Method for measuring the average diameter of the Al phase) The average diameter of the Al phase in the L cross section of the Al joint material was measured using a method that combined the information on the Al and Si concentrations obtained by SEM-EDS with the information on the crystal orientation obtained by EBSD, in the same way as in the measurement of the shapes of the Si and Al phases.
[0095] In detail, after carrying out the above procedures (1) and (2), the measurement was carried out according to the following procedure (3). (3) The crystal orientation of the region identified as Al phase was analyzed, and if the orientation difference between the measurement points was 15° or more, it was determined to be a grain boundary, and the circle equivalent diameter of each crystal grain was calculated. The circle equivalent diameters of each crystal grain were then averaged to calculate the average diameter of the Al phase. Here, the average value calculated by area averaging was used for the average calculation. In addition, when calculating the average diameter of the Al phase in the L cross section, only Al phases with a diameter (circle equivalent diameter) of 0.5 μm or more were considered.
[0096] The average diameter of the Al phase was determined as the average value of the values obtained for the three measurement regions by the above steps (1) to (3).
[0097] (Evaluation method for Al connecting materials) The evaluation method of the Al connecting material will be explained. The wire diameter of the Al connecting material (Al bonding wire) used for the evaluation was Φ300μm. The semiconductor chip used was made of Si, and the electrodes on the semiconductor chip were made of an alloy with a composition of Al-0.5%Cu, which was deposited to a thickness of 4μm. The substrate used was an Al alloy with a Ni film deposited to a thickness of 15μm. A commercially available wire bonder (manufactured by Ultrasonic Industries Co., Ltd.) was used to bond the Al connecting material, and both the 1st and 2nd bondings were wedge bonded.
[0098] (Method of evaluating reliability of high-speed temperature cycles) A commercially available high-speed thermal shock tester was used to evaluate the high-speed temperature cycle test (high-speed TCT). In the high-speed TCT, hot air is blown onto the sample to rapidly heat it up. The sample to be subjected to the high-speed TCT has a structure in which a semiconductor chip is mounted on a substrate, and the electrodes on the semiconductor chip and the electrodes on the substrate are connected with an Al connecting material. The sample placed in the sample chamber of the high-speed thermal shock tester was repeatedly subjected to thermal loads, with heating and cooling being one cycle. The minimum temperature during cooling was -50°C, and the maximum temperature during heating was 175°C. The heating time, including the heating time, was 20 seconds, and the cooling time, including the cooling time, was 40 seconds. After the start of the test, the sample was taken out after 10,000 cycles, and a shear strength test of the 1st joint was performed. The shear strength value of the 1st joint used to evaluate the high-speed temperature cycle reliability was the average value of the shear strength of 10 randomly selected 1st joints. The ratio (percentage) of the average shear strength after the high-speed TCT to the average shear strength before the test was taken as the strength retention rate. The higher the strength retention rate, the better the reliability of the joint. A strength retention rate of 85% or more was judged to be excellent and given a rating of "3," 75% or more but less than 85% was judged to be excellent and given a rating of "2," 70% or more but less than 75% was judged to require improvement and given a rating of "1," and less than 60% was judged to be problematic in practical use and given a rating of "0." "3" and "2" were judged to be pass, while "1" and "0" were judged to be fail. The evaluation results are shown in the "High-speed temperature cycle reliability (10,000 times)" column in the table. The temperature cycle reliability requirement for next-generation power semiconductor devices corresponds to 10,000 cycles.
[0099] (1st bonding strength evaluation method) The evaluation method of the 1st bond strength is explained below. The 1st bond strength was evaluated by a shear strength test. The 1st bond was performed at 10 places under general bonding conditions, and the shear strength of the 1st bond was measured. A commercially available micro shear strength tester (Nordson 4000-PLUS) was used to measure the shear strength. The shear speed was 200 μm / sec, and the height of the shear tool was 10 μm from the electrode surface. The shear strength was measured by fixing the substrate to which the Al wiring material was bonded with a jig. If the average value of the shear strength of the 10 1st bonded places was 1600 gf or more, it was judged to be excellent and rated as "3", if it was 1400 gf or more and less than 1600 gf, it was judged to be practically acceptable and rated as "2", if it was 1000 gf or more and less than 1400 gf, it was judged to need improvement and rated as "1", and if it was less than 1000 gf, it was judged to be practically problematic and rated as "0". The evaluation results are shown in the "1st bonding strength" column in the table.
[0100] (Method of evaluating wire breakage during processing) The method for evaluating wire breakage during processing is explained below. Wire drawing was performed from a wire diameter of 6 mmφ to a wire diameter of 0.3 mmφ, and the number of wire breakages was confirmed. The wire drawing conditions, such as the feed rate and area reduction rate, were selected from the conditions described above, and the manufacturing conditions were adjusted and changed appropriately for each wire. The length of the drawn Al connector was in the range of 100 to 200 m, and the number of wire breakages was calculated by converting it to per 100 m. If the number of wire breakages was 0, it was judged to be good and rated "3." If it was 1, it was judged that it could be dealt with by improving the manufacturing conditions and rated "2." If it was 2 to 4, it was considered that there was a problem with reduced productivity and rated "1." If it was 5 or more, it was judged that it was difficult to put into practical use and rated "0." The evaluation results are shown in the "Wire breakage during processing" column in the table.
[0101] (Method for evaluating the stability of the bond strength of the 2nd bond) Shear strength tests were conducted on 30 randomly selected 2nd joints, and the joint strength was obtained and the population standard deviation (σ) was calculated. If σ was 70gf or more, it was judged to be problematic in practical use and rated "0", if σ was between 50gf and 70gf, it was judged to be good and rated "1", if σ was between 30gf and 50gf, it was judged to be excellent and rated "2", and if σ was less than 30gf, it was judged to be particularly excellent and rated "3". "0" is a failure, and "1", "2", and "3" are passes. The evaluation results are shown in the "Stability of joint strength of 2nd joint" column in the table.
[0102] (Evaluation method for surface scratches and scrapes) The surface quality of the Al connector was evaluated with attention to scratches and chipping. The wire diameter of the Al connector was 0.3 mmφ. Three measurement areas were randomly selected at intervals of 1 m or more along the central axis of the Al connector, and three pieces of approximately 2 cm were taken from each of the three areas, for a total of nine samples. The surface was observed at a magnification range of 50 to 500 times with an SEM. Scratches longer than 50 μm and chipping longer than 30 μm were judged to be defective. The number of scratches and chips was counted, and if there were zero, it was judged to be good and passed, and was rated as "3," if there were two or less, it was judged to be no problem in practical use, and was rated as "2," if there were three to seven, it was judged to have poor surface quality, and was rated as "1," and if there were eight or more, it was judged to be difficult to use, and was rated as "0." The evaluation results are shown in the "Surface Quality" column in the table.
[0103] The evaluation results of the examples and comparative examples are shown in Tables 1 to 3.
[0104] [Table 1]
[0105] [Table 2]
[0106] [Table 3]
[0107] All of the Al connecting materials of Examples 1 to 47 contain 3.0 mass% or more and 12.0 mass% or less of Si, and at least one element from the first group (Sr, Eu, Na) in a total amount of 5 mass ppm or more and 800 mass ppm or less, and the shape ratio (e / f) of the Si phase in the L cross section is in the range of 0.25 to 0.65, and it has been confirmed that they exhibit good temperature cycle reliability even in high-speed TCT as well as good 1st bonding strength. In addition, it was confirmed that the Al connecting materials of Examples 1 to 22, 24 to 39, and 41 to 47, in which the shape ratio (c / d) of the Al phase in the L cross section is 0.25 or more and 0.7 or less, can reduce the frequency of wire breakage during processing. It was confirmed that the Al connecting materials of Examples 1 to 8, 10 to 43, and 45 to 47, in which the average diameter of the Al phase in the L cross section was 5 μm or more and 40 μm or less, tended to result in better results in terms of the joint strength stability of the 2nd joint. Furthermore, it was confirmed that the Al connecting materials of Examples 28 to 41 and 43 to 47, which contain a total of 5 mass ppm or more and 700 mass ppm or less of one or more of the second element group (Fe, Mg, Mn, Ga, Ge), have a smooth surface with reduced surface scratches and chipping. On the other hand, it was confirmed that the Al connecting materials of comparative examples No. 1 to 10 had either the Si concentration, the concentration of the first element group, or the shape ratio (e / f) of the Si phase outside the range of the present invention, and therefore either the temperature cycle reliability or the 1st bonding strength was insufficient.
Claims
1. An Al connecting material containing 3.0 mass% or more and 12.0 mass% or less of Si, and containing at least one of Sr, Eu, and Na in a total amount of 5 mass ppm or more and 800 mass ppm or less, with the remainder being Al and inevitable impurities, An Al connecting material, in which the average area ratio (e / f) of the short side length e to the long side length f of the Si phase in an L cross section (a cross section in the central axis direction including the central axis) of the Al connecting material is 0.25 or more and 0.65 or less.
2. Contains 3.0 mass% or more and 12.0 mass% or less of Si, and contains at least one of Sr, Eu, and Na in a total amount of 5 mass ppm or more and 800 mass ppm or less, Further, the material contains one or more of Fe, Mg, Mn, Ga, and Ge in a total amount of 700 ppm by mass or less, The balance of the Al connecting material is Al and inevitable impurities, An Al connecting material, in which the average area ratio (e / f) of the short side length e to the long side length f of the Si phase in an L cross section (a cross section in the central axis direction including the central axis) of the Al connecting material is 0.25 or more and 0.65 or less.
3. An Al connecting material for a semiconductor device, comprising 3.0 mass% or more and 12.0 mass% or less of Si, and a total of 5 mass ppm or more and 800 mass ppm or less of Sr, Eu, and Na, An Al connecting material for semiconductor device, in which the average area ratio (e / f) of the short side length e to the long side length f of the Si phase in an L cross section (a cross section in the central axis direction including the central axis) of the Al connecting material is 0.25 or more and 0.65 or less.
4. The Al connecting material according to any one of claims 1 to 3, wherein the average value of the area average of the ratio (c / d) of the short side length c to the long side length d of the Al phase in the L cross section is 0.25 to 0.
7.
5. The Al connecting material according to any one of claims 1 to 3, wherein the average diameter of the Al phase in the L cross section, as determined by the area average, is 5 µm or more and 40 µm or less.
6. An Al connecting material as described in claim 2, wherein the total concentration of Fe, Mg, Mn, Ga, and Ge is 5 ppm by mass or more.
7. The Al connecting material according to claim 3, further containing at least one of Fe, Mg, Mn, Ga, and Ge in a total amount of 5 ppm by mass to 700 ppm by mass.
8. The Al connecting material according to claim 3 or 7, wherein the total concentration of elements other than Al, Si, Sr, Eu, Na, Fe, Mg, Mn, Ga and Ge (hereinafter referred to as "other elements") in the Al connecting material is 0.5 mass% or less.
Citation Information
Patent Citations
Microalloyed Al-Si alloy and preparation method of aluminium alloy rod adopting microalloyed Al-Si alloy
CN105331856A
High-performance Al-Si welding wire alloy including trace La elements and preparation method of high-performance Al-Si welding wire alloy
CN110656263A
Manufacture of bonding strand for semiconductor element
JP1984057440A
Aluminum alloy thin wire for power-semiconductor device
JP2014129578A
Bonding wire, connection structure, semiconductor device and method of manufacturing the same
JP2014131010A